The stability of the Johnson-Mehl-Avrami equation parameters - Magnani, R. [UNESP]; Adorno, A. T. [UNESP] (Springer Nature, 1995)
The stability of the parameters of the Johnson-Mehl-Avrami equation was studied using two parametrizations of the sigmoidal function and its fit to some kinetic data. The results indicate that one of the forms of the function has more stable parameters and only for this form it is reasonable to use, as an approximation, the linear regression theory to analyse the parameters. © 1995 Chapman & Hall.
Keywords: Approximation theory; Mathematical models; Parameter estimation; Regression analysis; System stability; Johnson-Mehl-Avrami equation; Sigmoidal function; Reaction kinetics